How to train your dragon - Ferrera, America, 1984-; Mintz-Plasse, Christopher, 1989-; Ferguson, Craig, 1962-; Butler, Gerard, 1969-; Baruchel, Jay, 1982-; Hill, Jonah, 1983-; Wiig, Kristen, 1973-; Sanders, Chris; Cowell, Cressida; DreamWorks Animation; DreamWorks Home Entertainment (Firm) ([United States] : DreamWorks Home Entertainment, 2010)
Hiccup is a Viking teenager who aspires to hunt dragons, but doesn't exactly fit in with his tribe's longstanding tradition of heroic dragon slayers. His world gets turned upside down when he encounters a dragon that challenges him and his fellow Vikings to see the world from an entirely different point of view.
Title from disc surface.
Based on the book by Cressida Cowell.
Bonus features: trailers, featurettes, and commentary.
Production designer, Kathy Altieri ; editors, Darren Holmes, Maryann Brandon ; music, John Powell.
America Ferrera, Christopher Mintz-Plasse, Craig Ferguson, Gerard Butler, Jay Baruchel, Jonah Hill, Kristen Wiig.
MPAA rating: PG; for sequences of intense action and some scary images, and brief mild language.
Keywords: Vikings -- Juvenile drama; Dragons -- Juvenile drama; Children's films; Films for the hearing impaired; Feature films; Animated films